Translation, Cross-cultural Adaptation and Validation of Ankylosing Spondylitis Disease Activity Score (Faridpur Medical College Journal, 2020)
Ankylosing Spondylitis Disease Activity Score (ASDAS) is a very important tool for measuring disease activity in patients with axial spondyloarthritis (axSpA). This study was aimed to develop a culturally adapted, valid and reliable Bengali version of questionnaire for the ASDAS. The original English ASDAS was translated into Bangla and adapted in the local socio-cultural context, following standard international recommendations. Content validity of the adapted Bangla version was assessed by the item-level & scale level content validity indices (I-CVI & S-CVI). A total 120 patients with axSpA were assessed in the study. For construct validity, correlation between ASDAS with BASDAI, ESR, CRP, Maastricht enthesitis score, physician's global assessment and BASMI was assessed by Spearman's rank correlation coefficient. Internal consistency and test-retest reliability were assessed using Cronbach's alpha coefficient and intraclass correlation coefficient respectively. I-CVI for each item was 1 and S-CVI was 1. ASDAS-ESR and ASDAS-CRP showed strong correlation (Spearman's correlation coefficient >0.5) with BASDAI, ESR, MASES and physician global assessment of disease activity. The scale demonstrated excellent internal consistency (Crohnbach's alpha=0.703) and test-retest reliability (ICC=0.98). The adapted Bangla version of the ASDAS demonstrated acceptable psychometric properties (validity & reliability) in Bangladeshi patients with axSpA.Faridpur Med. Coll. J. Jul 2019;14(2): 62-66